Peripartum Phenomenon in Crioula Lanada Sheep Susceptible and Resistant to Gastrointestinal Nematodes - Pereira, Fabiellen Cristina; Longo, Cibele; Castilho, Caliê; Leme, Denise Pereira; Seugling, Jaqueline; Bassetto, César Cristiano; Amarante, Alessandro F. T.; Bricarello, Patrizia Ana (Frontiers in Veterinary Science, 2020)
The objective of this study was to evaluate parasitological and blood parameters in native breed Crioula Lanada sheep, to identify and compare individuals which are susceptible and resistant to gastrointestinal nematodes; these individuals belonging to the same herd in Santa Catarina, during gestation and lactation phases. For this purpose, 18 Crioula sheep were used within two years of evaluation. Blood samples and faeces were taken, animals were weighed from their 4th month of gestation until the weaning of their lambs, in the 4th month postpartum. Faeces were used for counting eggs per gram of faeces (EPG) and blood was used for analysis of packed cell volume, eosinophil count, total plasma protein, and immunoglobulin level IgG. From the EPG result, groups of ewes considered resistant and susceptible were identified and separated. The Kruskal Wallis nonparametric comparison test was used to evaluate the differences between days of parturition and linear mixed-effects model using package lme4 in R to evaluate the groups. Some difference has been verified regarding the EPG between these two groups, but in relation to further evaluated parameters, there was only difference within each group according to the progress of the studied phases. During peripartum and lactation, Crioula Lanada sheep from this study presented a variable immune response but including some animals with high resistance to the gastrointestinal nematodes. The physiological response of sheep to nematode infection is a useful tool to identify more susceptible individuals within the same breed and herd and to genetically select more resistant individuals.